The Effect of “Isi Piringku” Counseling with Video Blog (Vlog) Media on The Knowledge and Attitude of Mothers Under Children About Feeding Children Aged 6—59 Months - Rachmat, Mochamad; Maila, Ishfahani; Marbun, Rosmida M (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Data from The United Nation Children’s Fund (UNICEF), shows more than 50% of toddler's deaths are related to malnutrition, and two-third of those are related to inappropriate feeding practice for babies and toddlers, such as MP-ASI (complementary feeding) that is too fast or too late was given. The proportion of food varies consumption among children 6-23 months in Indonesia is 46,6%. The prevalence of stunting in Indonesia by 2018 is 30,8%. “Isi Piringku (My Plate)” is one of the implementations of dietary arrangements in accordance with balanced nutrition which was coined by The Ministry of Health in 2017 as a substitute of “4 Sehat 5 Sempurna (Healthy Four Perfect Five)”. Video Blog is one of the media that stimulates the senses of sight and hearing. The purpose of this research is to determine the differences in knowledge and attitude of mothers before and after counseling about “Isi Piringku (My Plate)” for toddlers (6-59 months) with video blog media.This research uses the Quasi Experimental Two Group Pre and Post Test Design. The intervention group was given counseling with vlog and the control group was not given any treatment (placebo) on the first day. The measurement of the final knowledge and attitude is done a week later. The results of this research shows that there were significant differences in knowledge and attitude before and after counseling with video blog in the intervention group with p knowledge p=0,000 (p<0,05) and p attitude p=0,000 (p<0,05). In addition, there were differences in knowledge and attitude of the intervention control groups after being treated with p knowledge p=0,000 (p<0,05) and p attitude p=0,000 (p<0,05). There is an effect of